Optimal portfolio selection- A case study of six financial institutions in Ghana. - Asare Kyei, Felicia (2016)
A thesis submitted to The Institute of Distance Learning, Kwame Nkrumah University of Science and Technology in partial fulfillment for the degree of Master of Science, in Industrial Mathematics.